Numerical study of turbulent mixed convection of nanofluids in three-dimensional horizontal concentric annuli - Alawi O.A.; Sidik N.A.C.; Dawood H.K. (American Scientific Publishers, 2023)
Cylinders (shapes); Finite volume method; Heat flux; Heat transfer; Mixed convection; Nanoparticles; Navier Stokes equations; Reynolds number; Volume fraction; Concentric annuli; Heat transfer characteristics; Hydraulic diameter; Nanofluids; Nanoparticle shape; Numerical results; SIMPLE algorithm; Turbulent mixed convections; Nanofluidics